SVC Placement for Voltage Profile Enhancement Using Self-Adaptive Firefly Algorithm - Selvarasu Ranganathan; Surya Kalavathi. M (Indonesian Journal of Electrical Engineering and Computer Science, 2014)
Static VAR Compensator (SVC) is one of the shunt type FACTS devices for providing reactive power support in power systems network and its placement representing the location and size has significant influence on enhancement of voltage profile. This paper presents a firefly algorithm based optimization strategy for placement of SVC in power systems with a view of minimizing voltage deviation at the load buses to enhance the load bus voltages. This method uses a self-adaptive scheme for tuning the firefly parameters. The proposed strategy is tested on three IEEE test systems. The obtained results are promising and show the effectiveness of the proposed approach.